Auditing - Millichamp, A. H. (Educational Low-Priced Sponsored Texts LondonGB, 2002)
Aims to simplify the theory and practice of modern auditing. Targets learners, including students preparing for the London Chamber of Commerce (LCC) and similar professional examinations. Includes strategies for succeeding at auditing examinations. Explains the rationale for auditing and looks at topics such as: professional rules, the conduct of the audit, audit evidence, review of financial statements, and the auditors' report.